Extracellular nucleotide metabolism in Leishmania: influence of adenosine in the establishment of infection - Fietto, Juliana Lopes Rangel; Marques-da-Silva, Eduardo de Almeida; Oliveira, Jamile Camargos de; Figueiredo, Amanda Braga; Lima Júnior, Djalma de Souza; Carneiro, Cláudia Martins; Afonso, Luís Carlos Crocco (Microbes and Infection, 2008)
Leishmaniasis is a parasitic disease with a variety of clinical forms, which are related to the Leishmania species involved. In the murine model, Leishmania amazonensis causes chronic non-healing lesions in Leishmania braziliensis- or Leishmania major-resistant mouse strains. In this study, we investigated the involvement of the pathway of extracellular nucleotide hydrolysis, with special focus on the role of extracellular adenosine, in the establishment of Leishmania infection. Our results show that the more virulent parasite—L. amazonensis—hydrolyzes higher amounts of ATP, ADP and AMP than the two other species, probably due to the higher expression of membrane NTPDase. Corroborating the idea that increased production of adenosine is important to lesion development and establishment of tissue parasitism, we observed that increased 5′-nucleotidase activity in L. braziliensis or addition of adenosine at the moment of infection with this parasite resulted in an increase in lesion size and parasitism as well as a delay in lesion healing. Furthermore, inhibition of adenosine receptor A2B led to decreased lesion size and parasitism. Thus, our results suggest that the conversion of ATP, a molecule with pro-inflammatory activity, into adenosine, which possesses immunomodulatory properties, may contribute to the establishment of infection by Leishmania.
Keywords: Leishmania; Ecto-nucleotidase; Adenosine; Extracellular; ATP